2005
DOI: 10.3171/spi.2005.2.3.0308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidural hypothermic saline infusion on locomotor outcome and tissue preservation after moderate thoracic spinal cord contusion in rats

Abstract: Object. Regionally delivered hypothermia has advantages over systemic hypothermia for clinical application following spinal cord injury (SCI). The effects of local hypothermia on tissue sparing, neuronal preservation, and locomotor outcome were studied in a moderate thoracic spinal cord contusion model. Methods. Rats were randomized to four treatment groups and data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…This has been most prominent in studies of spinal cord cooling to prevent injury during aortic cross-clamping. Casas et al 15 used cold saline infusion to achieve epidural temperatures in rats as low as 24°C but did not measure subarachnoid or spinal cord temperatures. In a group of studies using a closed hypothermic system in pigs, Mori et al 16 used a closed-loop catheter system to circulate iced saline in the epidural space to achieve subarachnoid cooling as low as 27.9°C.…”
Section: Discussionmentioning
confidence: 99%
“…This has been most prominent in studies of spinal cord cooling to prevent injury during aortic cross-clamping. Casas et al 15 used cold saline infusion to achieve epidural temperatures in rats as low as 24°C but did not measure subarachnoid or spinal cord temperatures. In a group of studies using a closed hypothermic system in pigs, Mori et al 16 used a closed-loop catheter system to circulate iced saline in the epidural space to achieve subarachnoid cooling as low as 27.9°C.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that systemic cooling hinders the re-entrance of damaged neurotransmitters into the spinal cord and increases spinal cord blood flow, as well as improves spinal cord cell survival rate [9,19,52,55]. However, inducing whole body cooling in humans can lead to adverse consequences.…”
Section: Introductionmentioning
confidence: 98%
“…Albin et al first documented a successful application of localized spinal cord cooling for experimental SCI in dogs by perfusing the injured spinal cord with isotonic saline (5°C) for 2.5 h [2]. Since then, there have been a number of promising experimental animal studies using similar cooling methods [1,3,4,7,9]. Recently, two other successful cooling techniques have been developed, which include using an epidural cooling catheter [34,37,42] and placing a cooling saddle directly onto the spinal cord [12,14,17,18,51].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960s, local profound hypothermia was produced in some patients by administering cold saline to the exposed spinal cord after laminectomy and during decompression surgeries [45,46]. These studies, along with experimental observations, provided important information regarding the ability to cool locally, and in some cases resulted in functional improvement [19,27,[47][48][49]. However, the interpretation of these studies was complicated by the fact that surgical interventions, including decompression procedures, may have led to some of the beneficial effects that were reported [46].…”
Section: Historical Perspectivementioning
confidence: 99%
“…In terms of SCI, published data have shown that relatively mild levels of hypothermia introduced after a traumatic or compressive SCI provides some degree of improvement in function and reduces the histopathological damage [22,[25][26][27][28][29][30][31][32][33][34][35][36][37]. In clinically relevant SCI studies, mild reductions in temperature have been shown to be protective, whereas mild elevations (hyperthermia) have been reported to worsen outcome [38][39][40].…”
Section: Introductionmentioning
confidence: 99%